2021
DOI: 10.5089/9781513585420.001
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Potential for Remittance Transfers: A Central America Perspective

Abstract: This paper analyzes the potential for fintech to facilitate cheaper and more efficient remittances, and to enhance financial inclusion in Central America. Digital remittances remain nascent in the region, primarily reflecting behavioral inertia, small cost advantages of digital over traditional channels, and inadequate financial literacy. Through expanded alliances between traditional and fintech operators, digital remittances can further reduce transaction costs and reach those remote, low-income households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Freund andSpatafora (2008) andOrozoco (2006) are among the earliest studies on remittance prices. Bersch et al (2021) find for a geographically more limited sample that remittance providers for Latin American destination countries are sensitive to price movements vis-a-vis their competitors, limited evidence for scale economies but lower fees in destination countries with higher levels of financial development. Da Silva Filho (2021) provides a recent and comprehensive review of the drivers of remittance costs.…”
Section: International Monetary Fundmentioning
confidence: 73%
“…Freund andSpatafora (2008) andOrozoco (2006) are among the earliest studies on remittance prices. Bersch et al (2021) find for a geographically more limited sample that remittance providers for Latin American destination countries are sensitive to price movements vis-a-vis their competitors, limited evidence for scale economies but lower fees in destination countries with higher levels of financial development. Da Silva Filho (2021) provides a recent and comprehensive review of the drivers of remittance costs.…”
Section: International Monetary Fundmentioning
confidence: 73%
“…Recent studies on digital money or fintech remittances for Central America reveal great potential for the region, for example, to lower transaction costs, which are still above the 3% mark envisaged in the Sustainable Development Goals set out by the United Nations (Bersch et al 2021;Carare et al 2022). However, the study by Alvarez et al (2022) finds no evidence for a significant use of Bitcoin to pay taxes of the transfer of remittances according to interviewees.…”
Section: Bitcoin As International Moneymentioning
confidence: 98%
“…The onset of cryptocurrencies coincided but also advanced promotion of financial technology (fintech), which is a broader term that encompasses blockchain and all other technologies used to enhance and improve financial services and processes. Bersch et al (2021) analysed the potential of fintech to facilitate cheaper and more efficient remittances, and to improve financial inclusion in Central America. They concluded that fintech facilitates cross-border payments, and that greater competition could further decrease fees.…”
Section: Transaction Fees In Bitcoin Network and For Bank Remittancesmentioning
confidence: 99%